Development and Evaluation of a Cloud-Based Electronic Medical Record Application to Improve Healthcare Service Efficiency - Susanto, Edy; Erna Zakiyah (Jurnal Inotera, 2024)
The problem often encountered in medical record services at hospitals is the inefficiency and ineffectiveness of processing registration data due to the continued use of manual bookkeeping as an archive. This leads to obstacles such as difficulties in retrieving patient data and the risk of data redundancy. When patients do not bring their medical cards, there is a risk of damage or loss of patient data, as well as the risk of data accumulation that requires special storage space. Therefore, this study developed a medical record information system using the waterfall method, which consists of requirements, design, implementation, verification, and maintenance phases. Based on the results of white box testing, the cyclomatic complexity is 21, region = 21, and independent path = 21, indicating that the system is functioning well without errors. Furthermore, User Acceptance Testing (UAT) resulted in a percentage of 81.5% from 10 respondents, indicating the system received positive feedback from users.